Automate crime news segmentation, knowledge-based generation and public opinion mining for social awareness - Sabit, Ahmed Bin; Ahsan, Asif; Tasnim, Zarin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.